Algoritem za izbiro ustreznega EMI filtra - Podberšič, Marko (Informacije MIDEM, 2003)
The article describes a new method of selection of a suitable EMI filter for a signal line. This method is based on measurement of FFT of a signal. The selection is rather good, because we optimise EMI filter for each signal line separately. This was presented on an example of a CPU module. We know actually three EMI filter selection methods. The first EMI filter selection method is based on a realization of EMI filters with a help of ground planes. All signal lines must be surrounded with ground (fig. 1). We can get so rather good capacitive draining of high frequency noise to the ground. Such capacitive draining is some sort of EMI filter. This capacitive draining is better if the coupling path between the signal line and the_ ground plan is longer. Many times this filter is not good enough. In these cases real EMI filters must be used. The second EMI filter selection method is based on a measurement of a radiation of whole equipment. At this method, we measure the radiation of whole equipment and get a discrete frequency component with maximum amplitude. We select EMI filters with maximum insertion loss at frequency, which is close by this frequency. We use EMI filters with similar characteristics on the whole equipment. The third EMI filter selection method is based on a measurement of a FFT on a single signal line. This method is described in this article. Some technical expressions are described in first chapters of this article. Such expressions are a critical line length, S parameters of two-input circuit, a typical frequency -observed as EMI, an input impedance of EMI filter, adjustment and filtering. An expression "critical line lengt" is known in the high-speed transmission-line theory. We determine a critical line length with help of the frequency Fknee (equation 14). At this critical line length the rise-time, Tr, exactly matches the propagation delay time, Tpd. This means that the transient phenomenon .formed by the low-to-high signal transition precisely fits the line length. For that reason, this distance is called the "length of the rising edge". We must stress that the critical line length Imax means two-way propagation delay (source-Ioad-source). A line length equal to or longer as the critical length certainly behaves as a transmission-line. This means that you must consider characteristic impedance, delayand reflections in that case. S parameters are almost always presented because EMI filters are usually two-input circuits. The letter S comes from an english word "Scattering". S parameters describes that an inca ming power in one input is distributed among all inputs of multi-input linear circuit. We are using these S parameters for an input impedance of the EMI filters calculation. Typical frequency - observed as EMI, depends upon used logic elements and microcontroller. Precisely, it depends upon rise time of signals, which are transmited by these elements (equation 35). We must be attentive when we select appropriate logic elements and microcontroller. If we use, for example,faster HCT instead of slower LS-TTL, the electromagnetic emission increases for up to three times. Of course this typical frequency finds expression at certain line length (emission radiation problem). These typical frequencies - observed as EMI are very important when we develop an electroniccircuit. A procedure of the new EMI filter selection method is as following: -Measuring the rise time tr of the signal -Calculating (or measuring) the typical frequency - observed as EMI -Selecting a suitable EMI filter family with regard to an application -Selecting an EMI filter from the family. We select the filter with maximum insertion loss at frequency, which is close by the typical frequency. The need of the EMI filters is conditional on the critical line length. This is verified by our experiences. If a two-wayline length is shorter to the previously calculated Imax (critical linelength) and there is no vias on the line, the usage of an EMI filter is not necessary. We have shown on a example of a CPU module that this new EMI filter selection method based on FFT measurements of signals is better then the old one based on a measurement of a radiation of the whole CPU module.
Keywords: CPU modul; EMC; EMI filtri; filtriranje; signali